Boldly go : reflections on a life of awe and wonder - Shatner, William; Brandon, Josh (Filmmaker) (New York : Atria Books, 2022)
"The beloved star of Star Trek, recent space traveler, and living legend William Shatner reflects on the interconnectivity of all things, our fragile bond with nature, and the joy that comes from exploration in this inspiring, revelatory, and exhilarating collection of essays"--
We belong together -- Listen to the animals -- Pieces of humanity -- It's round. I checked. -- Listen to the music -- The worst and the best -- There's beauty in everything -- Your place in the universe -- When I'm gone.
Keywords: Shatner, William; Actors -- Canada -- Biography; Essays; Autobiographies